XIV Mediterranean Conference on Medical and Biological Engineering and Computing 2016 MEDICON 2016, March 31st-April 2nd 2016, Paphos, Cyprus - Kyriacou, Efthyvoulos; Christofides, Stelios; Pattichis, Constantinos S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume presents the proceedings of Medicon 2016, held in Paphos, Cyprus. Medicon 2016 is the XIV in the series of regional meetings of the International Federation of Medical and Biological Engineering (IFMBE) in the Mediterranean. The goal of Medicon 2016 is to provide updated information on the state of the art on Medical and Biological Engineering and Computing under the main theme "Systems Medicine for the Delivery of Better Healthcare Services". Medical and Biological Engineering and Computing cover complementary disciplines that hold great promise for the advancement of research and development in complex medical and biological systems. Research and development in these areas are impacting the science and technology by advancing fundamental concepts in translational medicine, by helping us understand human physiology and function at multiple levels, by improving tools and techniques for the detection, prevention and treatment of disease. Medicon 2016 provides a common platform for the cross fertilization of ideas, and to help shape knowledge and scientific achievements by bridging complementary disciplines into an interactive and attractive forum under the special theme of the conference that is Systems Medicine for the Delivery of Better Healthcare Services. The programme consists of some 290 invited and submitted papers on new developments around the Conference theme, presented in 3 plenary sessions, 29 parallel scientific sessions and 12 special sessions.
Message -- Information For Oral Presentations -- Information For Short Paper Presentations -- Medicon 2016 Preliminary Schedule -- Registration Times & Pre-Conference Meetings -- Preliminary Programme -- Medicon 2016: Students Paper Competition Finalists (Top 10) -- Plenary Sessions.
Keywords: Biomedical engineering; Medical physics; Biomaterials; Biomedical Engineering and Bioengineering; Medical Physics; Biomaterials